2017
DOI: 10.1002/ep.12818
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis and performance improvement of Irem geothermal power plant in Turkey: A case study of organic Rankine cycle

Abstract: Renewable and environmentally friendly energy sources are becoming increasingly important nowadays. This growth in importance also has an effect on the energy conversion systems using more eco‐friendly and renewable energy sources (geothermal, wind, solar) than fossil fuels, the use of which has been reduced these days (oil, coal, natural gas, etc.). From this perspective, renewable energy sources and the conversion efficiency of the facilities which use these sources have also gained importance. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This behavior is explained by the fact that in the analyzed plant the condenser was cooled by air instead of water, as used by the other authors. Unverdi and Cerci [62] analyzed a similar system installed in Turkey using n-pentane; in this case, the energy and exergy efficiencies were 5.89% and 33.8%, respectively.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…This behavior is explained by the fact that in the analyzed plant the condenser was cooled by air instead of water, as used by the other authors. Unverdi and Cerci [62] analyzed a similar system installed in Turkey using n-pentane; in this case, the energy and exergy efficiencies were 5.89% and 33.8%, respectively.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The optimization of parallel distribution between domestic heat and electricity supplying via geothermal energy was studied by Marty et al [14] where a sensitivity analysis was also carried out using the source condition. Thermodynamic enhancement of the Irem binary power station located in Germencik, Turkey was performed in [15] by employing an ORC considering different working fluids. In the same work, it was demonstrated that the optimum ambient temperature corresponding to the maximum exergy efficiency is 18.5 °C.…”
Section: Introductionmentioning
confidence: 99%